Characteristics Study Of Emulsified Biofuel And Egg Yolk Oil (EBEYO) Properties And Its Performance In Compression-Ignition Engine Using New Formulated Surfactants And Composition - Alauden, Muhammad Rafiq (Universiti Sains Malaysia, 2022)
Increasing fossil fuel price and government initiatives to cut greenhouse gas emissions have led to a rise in demand for biofuel. In contrast to fossil fuels, which are finite resources, biofuels are created from feedstocks that are continually replenished by nature. Biofuel has a high oxygen content and burning it in the engine has improve emissions indirectly. However, straight application of biofuel to the engine is absolutely restricted since it will harm the engine by causing carbon deposits, injector clogging, and incomplete combustion. Hence, proper emulsification of biofuel with the addition of surfactant and water is required to produce better physicochemical properties such as density, viscosity, and calorific value comparable to the baseline diesel fuel. The previous experiment uses surfactant Tween 80 and Span 80 for emulsification. While for this project, surfactants (Triton X-100 and Span 80) were used with constant of 2% composition and the egg yolk oil (EYO) addition with different percentages (5%, 10%, 15%, 20% and 25%) volumes in the emulsified biofuel (EB). The effect of the EB blend on the physicochemical properties and engine performance was studied. For the physicochemical properties test, the results show that the addition from 5% to 25% volumes of EYO into EB reduce the viscosity by 4.53%, for density by 1.27% and increase the calorific value by 0.3% compared to neat EB (RPO100EYO). EBEYO 4 (RPO80EYO20) has the lowest density with 1.27% drop and highest calorific value with 0.3% gain when compared to EB fuel. The percentage difference in the physicochemical criteria between EBEYO and baseline diesel fuel is by 6.68% for density, 87.2% for viscosity and 11.9% for calorific value. Based on the engine performance test by EBEYO fuel samples, the torque and brake power output were both 29.2% lower and the brake specific fuel consumption (BSFC) was 9.71% lower than with baseline diesel because of the lower heating value. Exhaust temperatures for EB and EBEYO’s are significantly lower than baseline diesel fuel resulting in less carbon release, low sulphur content, which contribute to less harmful emissions. Besides that, the fuel consumption of EBEYO fuel samples is better than diesel fuel resulting in reduction of brake specific fuel consumption (9.71 %) and increment in the brake thermal efficiency (10.11%) as the speed of the engine increase. Overall, this study demonstrates that EBEYO 3 (RPO85EYO15) application in CI engine is the most efficient fuel to be used and has been identified as a viable new source of biofuel for the future fuel replacement.